Interleukin-22 Deficiency Contributes to Dextran Sulfate Sodium-Induced Inflammation in Japanese Medaka, Oryzias latipes - Takahashi, Yoshie; Okamura, Yo; Harada, Nanaki; Watanabe, Mika; Miyanishi, Hiroshi; Kono, Tomoya; Sakai, Masahiro; Hikima, Jun-ichi (Frontiers in Immunology, 2021)
Mucosal tissue forms the first line of defense against pathogenic microorganisms. Cellular damage in the mucosal epithelium may induce the interleukin (IL)-22-related activation of many immune cells, which are essential for maintaining the mucosal epithelial barrier. A previous study on mucosal immunity elucidated that mammalian IL-22 contributes to mucus and antimicrobial peptides (AMPs) production and anti-apoptotic function. IL-22 has been identified in several teleost species and is also induced in response to bacterial infections. However, the roles of IL-22 in teleost immunity and mucus homeostasis are poorly understood. In this study, Japanese medaka (Oryzias latipes) was used as a model fish. The medaka il22, il22 receptor A1 (il22ra1), and il22 binding protein (il22bp) were cloned and characterized. The expression of medaka il22, il22ra1, and il22bp in various tissues was measured using qPCR. These genes were expressed at high levels in the mucosal tissues of the intestines, gills, and skin. The localization of il22 and il22bp mRNA in the gills and intestines was confirmed by in situ hybridizations. Herein, we established IL-22-knockout (KO) medaka using the CRISPR/Cas9 system. In the IL-22-KO medaka, a 4-bp deletion caused a frameshift in il22. To investigate the genes subject to IL-22-dependent regulation, we compared the transcripts of larval medaka between wild-type (WT) and IL-22-KO medaka using RNA-seq and qPCR analyses. The comparison was performed not only in the naïve state but also in the dextran sulfate sodium (DSS)-exposed state. At the transcriptional level, 368 genes, including immune genes, such as those encoding AMPs and cytokines, were significantly downregulated in IL-22-KO medaka compared that in WT medaka in naïve states. Gene ontology analysis revealed that upon DSS stimulation, genes associated with cell death, acute inflammatory response, cell proliferation, and others were upregulated in WT medaka. Furthermore, in DSS-stimulated IL-22-KO medaka, wound healing was delayed, the number of apoptotic cells increased, and the number of goblet cells in the intestinal epithelium decreased. These results suggested that in medaka, IL-22 is important for maintaining intestinal homeostasis, and the disruption of the IL-22 pathway is associated with the exacerbation of inflammatory pathology, as observed for mammalian IL-22.